Topological Control of Porous Silicon Photonic Crystals by Microcontact Printing. Issue 7 (26th May 2013) - Ruminski, Anne M.; Barillaro, Giuseppe; Secret, Emilie; Huang, Winnie D.; Potocny, Andrea; Carion, Ulysse; Wertans, Charles; Sailor, Michael J.
<x xml:space="preserve">Abstract</x> Free‐standing, uniformly wrinkled multilayered photonic crystals are prepared in porous Si by conformal electrochemical etch of a highly doped p++ type Si wafer that is pre‐shaped with periodic grooves. The grooves are prepared by first microcontact printing a parallel line of oligomeric polydimethylsiloxane and then electrochemically etching the patterned wafer. The etch proceeds anisotropically, with the resist‐covered regions etching more slowly than the resist‐free regions. The grooved substrate is then etched using a sinusoidal current density waveform, generating a porosity‐modulated photonic crystal (rugate filter) that is conformal with the grooves. This porous multilayer is then removed, resulting in a freestanding nanostructure with a corrugated topological modulation in the x–y plane and a rugated porosity modulation in the z‐direction. In addition to the resonant photonic reflectance signature from the porosity‐modulated rugate filter (along the z direction), the structures display optical diffraction in transmission from the x–y plane due to the spatially modulated grooves. The silicon wafer that remains after removal of the porous multilayer still contains a rippled surface, allowing the process to be repeated without additional microcontact printing. Six generations of freestanding, three‐dimensional diffraction gratings are produced from a single wafer and only one initial patterning step.